A Longitudinal Lifecycle Assessment of Micro-Real Estate Assets: Strategic Optimization of Net Operating Income (NOI) Through Value-Add Repositioning - Korinnyi, Oleksandr (Global Prosperity, 2025)
This research is directed toward the development of an algorithm enabling investors to pivot from initial cost minimization to the optimization of the total cost of ownership and the maximization of NOI through the implementation of long-term technological solutions. The study is predicated upon a 15-year planning horizon and an empirical analysis of 7 representative assets across diverse U.S. climatic zones. The methodology synthesizes dynamic financial modeling (NPV, IRR, WACC), stochastic Monte Carlo simulations for risk assessment and sensitivity analysis regarding mortgage rate fluctuations and fiscal incentives under the Inflation Reduction Act (IRA). A stratified sampling technique and data triangulation based on EIA, HUD and Yardi Matrix reports are employed. It is demonstrated that the application of the LCCA methodology facilitates an 18-25% growth in NOI and a 30-40% reduction in operating expenses (OPEX). The utilization of high-durability materials and Smart HVAC systems mitigates turnover costs and bolsters tenant retention by 20%. Findings indicate that technological modernization induces cap rate compression of 50-70 basis points, augmenting the asset`s exit value by 10-12% and shielding capital against "brown discounting" risks. Within the context of the 2026 U.S. market, the LCCA methodology evolves from an analytical instrument into a strategic cornerstone for small-scale investor survival. It enables the conversion of capital expenditures (CAPEX) into highly liquid assets, ensuring financial antifragility, access to green financing and alignment with ESG standards.